MUSCLE AND SKIN AMINO ACID COMPOSITIONS OF THE GREATER CANE RAT (THRYONOMYS SWINGERIANUS) - E.I. ADEYEYE,; R.O. JEGEDE, (International Journal of Pharma and Bio Sciences, 2010)
The Greater Cane Rat muscle and skin samples were evaluated for their amino acid profiles. The amino acid values were (in mg/g crude protein): highest concentrated amino acid was glutamic acid (150; muscle) and 140 (skin) with highest essential amino acid as leucine (72.2; muscle) and 69.0 (skin). Total essential amino acids (mg/g crude protein): 382(42.9 %) muscle and 350 (47.6 %) skin. The limiting amino acid on whole hen’s egg score was threonine (0.39; muscle) and serine (0.39; skin); on provisional scoring pattern, it was threonine (0.50) muscle and 0.75 (skin); on pre-school child requirement, it was threonine (0.59) in muscle but lysine (0.69) in skin. Significant differences existed between the amino acid profiles at r = 0.05 and n-2; total amino acid levels being 891 mg/g crude protein (muscle) and 736 mg/g crude protein (skin).